Procedimientos de auditoría en el sector transportista, en el cantón La Maná, provincia de Cotopaxi - Zambrano Fernández, Gabriela Agustina (2016)
This research topic was held at Cooperativa de Transporte de Pasajeros Intraprovincial “Río San Pablo” located at Av. Amazonas and San Pablo. The problem was determined in the lack of implementation of audit procedures for the proper control of the administrative management of the institution. The general objective was set to apply a Model of Audit Procedures in the transport sector in Canton La Mana, Cotopaxi Province. Their specific objectives are: to analyze the management of the departments in the different sectors of Transport, diagnose the current situation of Transportation Sector and design a Model Audit Procedures in the transport sector….